Relationship Physical Aspect and Policy Nerve Inpatient Service with Patient Satisfaction at Cut Nyak Dhien Regional General Hospital Aceh Barat Regency - Nurhayati, Nurhayati; Fera, Dian; Marniati, Marniati; Farisni, Teungku Nih; Nabela, Danvil (Universitas Teuku Umar, 2022)
Patient satisfaction is one of the first indicators of hospital’s standards, and a measure of service quality. The quality of health services is health services that can lead to patient satisfaction in every patient, where the procedures for implementation are in accordance with established standards and codes of ethics. The purpose of this research problem is to determine the relationship between physical and policy aspects with patient satisfaction at the Cut Nyak Dien Hospital in West Aceh.This research uses descriptive quantitative with cross sectional design. The population in this study were 855 patients or their guardians, the sampling technique used the type of accidental sampling using the Slovin formula to produce 90 respondents who had been hospitalized for 1x24 hours in June- August 2021. To analyze the data, the researcher used univariate and bivariate tests using Chi-square test, obtained p-value: 0,855 (p-value > α = 0,05) for the physical aspect and p-value = 0,049 (p-value < α = 0,05) for the policy. So, it can be concluded that there is no significant relationship between physical aspect with patient satisfaction, there is a significant relationship between policy and patient satisfaction, follow-up by providing intervention to socialize the implementation of health services according to standard operating procedures